SYNTHESIS AND STUDY OF URANILE COORDINATION COMPOUNDS WITH DERIVATIVES OF 3-(2-HYDROXYPHENIL)-1,2,4-TRIAZOLE: UDC 547+546.712'742'562 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Several complex-compounds based on derivatives of 3-(2-hydroxyphenyl)-1,2,4-triazole  were synthesized. Obtained compounds were studied by means of NMR-spectroscopy. The structure of synthesized complexes were offered according to the  results
Keywords: 1,2,4-Triazole, deprotonation, uranile